Simulasi Numerik Kapal Katamaran Pendeteksi Kedalaman Banjir Menggunakan Software Maxsurf Untuk Mencari Resistance - Rinasa Agistya Anugrah; Muhammad Panji Awwaludien Al-Fath (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
Indonesia is a country prone to natural disasters, one of the most frequent natural disasters is flooding. when there is a flood in an area, it is necessary to measure the depth of the flood, this serves to reduce the occurrence of accidents when a flood occurs. To reduce this risk, a vessel that measures flood depths is designed using a catamaran hull, then the design results will be simulated using the software. Design and numerical simulation in this study using Maxsurf software. The trial and error method is used to determine the size of the ship. By using Maxsurf software, several parameters can be known including resistance, power, and displacement. In the calculation of the resistance in this study using the Holtrop method, the ship's speed has variations with speed (0.5, 1, 1.5, 2, and 2.5). The design of the ship with a displacement of 1,665 kg, obtained the main size of the ship Length: 60 cm; Breadth: 30 cm; Depth:15 cm; Draft: 6 cm. Based on the results of the numerical simulation, the resistance with a speed of 0.5 m/s gets 0.46 N, 1 m/s gets 1.6 N, 1.5 m/s gets 3.18 N, 2 m/s gets 4.92 N, and 2.5 m/s get 6.89 N From the results obtained the graph will form a linear trend. Thus the speed of the ship will affect the resulting resistance. The higher the speed of the ship, the greater the resulting resistance.